Putative Contribution of 8-Aminoquinolines to Preventing Recrudescence of Malaria - Miles B. Markus (Tropical Medicine and Infectious Disease, 2023)
Enhanced therapeutic efficacy achieved in treating Plasmodium vivax malaria with an 8-aminoquinoline (8-AQ) drug such as primaquine (PQ) together with a partner drug such as chloroquine (CQ) is usually explained as CQ inhibiting asexual parasites in the bloodstream and PQ acting against liver stages. However, PQ’s contribution, if any, to inactivating non-circulating, extra-hepatic asexual forms, which make up the bulk of the parasite biomass in chronic P. vivax infections, remains unclear. In this opinion article, I suggest that, considering its newly described mode of action, PQ might be doing something of which we are currently unaware.